NVX-CoV2373-induced T- and B-cellular immunity in immunosuppressed people with multiple sclerosis that failed to respond to mRNA and viral vector SARS-CoV-2 vaccines - Mueller-Enz, Magdalena; Woopen, Christina; Katoul Al Rahbani, Georges; Haase, Rocco; Dunsche, Marie; Ziemssen, Tjalf; Akgün, Katja (Frontiers in Immunology, 2023)
Importance: Immunological response to SARS-CoV-2 vaccination is important especially in people with multiple sclerosis (pwMS) on immunosuppressive therapies. Objective: To determine whether adjuvanted protein-based vaccine NVX-CoV2373 is able to induce an immune response to SARS-CoV-2 in pwMS with inadequate responses to prior triple mRNA/viral vector vaccination. Design, Setting, Participants: We conducted a single center, prospective longitudinal cohort study at the MS Center Dresden, Germany. Sixty-five participants were included in the study in accordance with the following eligibility criteria: Age >18 years, immunomodulatory treatment, insufficient Tcellular and humoral response to prior vaccination with at least two doses of SARS-CoV-2 mRNA (BNT162b2, mRNA-1273) or viral vector vaccines (AZD1222, Ad26.COV2.S). Interventions: intramuscular vaccination with two doses of NVX-CoV2373 at baseline and three weeks follow-up. Main Outcomes and Measures: Development of SARS-CoV-2 specific antibodies and T cell response was evaluated. Results: For the final analysis, data from 47 patients on stable treatment with sphingosine-1phosphate receptor (S1PR) modulators and 17 on ocrelizumab were available. Tolerability of NVX-CoV2373 vaccination was overall good and comparable to the one reported for the general population. After second NVX-CoV2373 vaccination, 59% of S1PR-modulated patients developed anti-spike IgG antibodies above predefined cut-off of 200 BAU/mL (1204.37 [693.15, 2092.65] BAU/ml; mean, 95% CI) whereas no clinically significant T cell response was found. In the subgroup of the patients on ocrelizumab treatment, 23.5% developed anti-spike IgG >200 BAU/mL NVX-CoV2373 vaccination in pwMS 2 (116.3 [47.04, 287.51] BAU/ml; mean, 95% CI), and 53% showed positive spike-specific T-cellular responses (IFN-gamma release to antigen 1 0.2 [0.11, 0.31] IU/ml; antigen 2 0.24 [0.14, 0.37]; mean, 95% CI) after the second vaccination. Conclusions: Vaccination with two doses of NVX-CoV2373 was able to elicit a SARS-CoV-2specific immune response in pwMS lacking adequate immune responses to previous mRNA/viral vector vaccination. For patients receiving S1PR modulators, an increase in anti-SARS-CoV-2 IgG antibodies was detected after NVX-CoV2373 vaccination, whereas in ocrelizumab-treated patients, the increase of antiviral T cell responses was more pronounced. Our data may impact clinical decision-making by the preference of NVX-CoV2373 vaccination in pwMS receiving treatment with S1PR modulation or anti-CD20 treatment.